ARDL Bounds Testing Approach to Cointegration: A Re-Examination of Augmented Fisher Hypothesis in an Open Economy - Alimi, R. Santos (Asian Journal of Economic Modelling, 2014)
This paper investigated the relationship between expected inflation and nominal interest rates in Nigeria and the extent to which the Fisher effect hypothesis holds, for the period 1970-2012. We attempted to advance the field by testing the traditional closed-economy Fisher hypothesis and an augmented Fisher hypothesis by incorporating the foreign interest rate and nominal effective exchange rate variable in the context of a small open developing economy, such as, Nigeria. We applied ARDL bound testing, vector error correction (VECM) and stability of the functions was also tested by CUSUM and CUSUMSQ. We found that full Fisher hypothesis does not hold but there is a Fisher effect in the case of Nigeria over the period under study. In the context of an open economy, the study showed that aside expected inflation, the international variables - foreign interest and nominal effective exchange rates - contain information that predict the nominal interest rate and it also suggested a feed-back mechanism between nominal interest rate and foreign interest rate. Finally, CUSUM test confirms the long-run relationships between the variables and also shows the stability of the coefficients.